Influences on diet and physical activity choices of 11–13-year-olds in a school setting. (August 2019) - McHugh, Camilla A; Anderson, Lindsey; Lloyd, Jenny; Logan, Stuart; Wyatt, Katrina
Objective: This paper uses a qualitative approach to explore the factors that influence diet and physical activity choices of 11–13-year-olds with a particular focus on the impact of the school environment. Design: Qualitative focus groups. Setting: Three purposively sampled secondary schools in Devon, UK. Method: A total of 53 students, aged 11–13, took part in six focus groups. Thematic, framework analysis was used to analyse the data. Result: Four overarching themes emerged: (1) health now and in the future; (2) the role of others; (3) provision, temptation and addiction; and (4) boundaries, strategies and support. Participants demonstrated good knowledge of what constitutes a healthy lifestyle and its importance for future health, although it was not necessarily seen as a priority at this stage of life. Key influences on their choices were their peers and family, although participants also identified that the school environment influences the food choices they make while there. Conclusion: In this study, 11–13-year-olds identified that schools could do more to support them to make healthier food choices. However, future research needs to understand the constraints schools face in terms of food provision in order to highlight possible opportunities for intervention.